Efficacy And Residual Effect Of Zeolite Granular Temephos Formulation And Monomolecular Film Oil Against Larvae And Pupae Of Aedes Albopictus (Skuse) (Diptera: Culicidae) - Mohamad, Nurhafiza (2010)

(untitled)
Efficacy and residual effect of a new formulation of temephos, a zeolite granular formulation (Azai) and monomolecular film oil (Agnique MMF) were conducted. Initially, an efficacy study was evaluated against larvae and pupae of Ae. albopictus in the laboratory and in the field by using black plastic pails (15 liters). The dosages for Azai used were 0.50ppm, 0.75ppm, 1.00ppm, 1.25ppm and 1.50ppm of a.i., while for Agnique MMF were 5.00ppm, 8.33ppm, 10.00ppm, 13.33ppm and 16.67ppm of a.i. In five days, all dosages of Azai showed higher percentages of larval mortality (%LM) compared to Agnique MMF. In contrast, all dosages of Agnique MMF were superior against pupae compared to Azai in the laboratory and the field.